The MCTG bank's fraud case: does anyone matter? - Abdullah, Amalina (Universiti Putra Malaysia Press, 2012)
This case discusses the issues related to violation of business ethics and the intentional fraud committed by banks’ employees. In addition, this case also addresses some issues on internal control system and code of ethics, and how these issues can be solved by the top management and at managerial level. Information about the company’s background and activities are highlighted to assist the case study for further discussion. Finally, the case explores some possible ways for the company to take appropriate action in order to enhance its reputation and mitigate fraud.